2003
DOI: 10.1093/mutage/18.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Statistics of the Comet assay: a key to discriminate between genotoxic effects

Abstract: The alkaline Comet assay is a widely used single cell gel electrophoresis technique for the quantification of DNA strand breaks, crosslinks and alkali-labile sites induced by a series of physical and chemical agents. DNA migration in an electric field, supposed proportional to strand breakage, is a proposed estimation of genotoxicity. Breaks are quantified from geometric and fluorescence measurements by image analysis of comet-shaped DNA, often reported parameters being tail DNA and tail moment. Although a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(78 citation statements)
references
References 44 publications
4
71
0
3
Order By: Relevance
“…White and Rasmussen, (1998) showed that TM has the advantage of considering damage expressed as a long tail with a low fraction of high fraction of DNA or a short tail with a highly fragmented DNA. There are another study revealed that tail length and tail moment can provide similar results (Duez et al, 2003).…”
Section: The Statistical Analysis Of Dna Damagementioning
confidence: 81%
See 1 more Smart Citation
“…White and Rasmussen, (1998) showed that TM has the advantage of considering damage expressed as a long tail with a low fraction of high fraction of DNA or a short tail with a highly fragmented DNA. There are another study revealed that tail length and tail moment can provide similar results (Duez et al, 2003).…”
Section: The Statistical Analysis Of Dna Damagementioning
confidence: 81%
“…Furthermore, TM has the upside of considering damage communicated as a short tail with a high division of DNA or a long tail with a low division of DNA (White and Rasmussen, 1998). According to Duez et al (2003) and Pereira et al (2010), the lower significance increase in TM data of the 4 th instar, pupae and male stages Elmansoreyah water stream may reflect the cells with DNA cross-linking lesions. From the above results, the tail moment more responsive than tail length, and these results agreed with data obtained by Pereira et al (2010).…”
Section: The Statistical Analysis Of Dna Damagementioning
confidence: 96%
“…Data were presented as box-and-whisker plots where the median value was illustrated as a line flanked by boxes within which 25% to 75% of the data fell and whiskers indicating 10% to 90% of the data range observed. In a cell culture study Duez et al [55] concluded that analysis of median comet data from repeated experiments is an efficient way to demonstrate genotoxic effects with ALA [55].…”
Section: Single Cell Gel Electrophoresismentioning
confidence: 99%
“…DNA migration in an electric field, supposed proportional to strand breakage, is a proposed estimation of genotoxicity. Breaks are quantified from geometric and fluorescence measurements by image analysis of comet-shaped DNA (Duez et al 2003). The Comet assay is a rapid, simple and sensitive technique for measuring DNA breakage with a small number of cells and detects intercellular differences in DNA damage Johanson 1984, 1987;Singh et al 1988).…”
Section: Discussionmentioning
confidence: 99%